Coronary flow velocity reserve predicts adverse prognosis in women with angina and no obstructive coronary artery disease: results from the iPOWER study. (1st December 2020) - Schroder, Jakob; Michelsen, Marie M; Mygind, Naja D; Suhrs, Hannah E; Bove, Kira B; Bechsgaard, Daria Frestad; Aziz, Ahmed; Gustafsson, Ida; Kastrup, Jens; Prescott, Eva
Abstract: Aims : Many patients with angina, especially women, do not have obstructive coronary artery disease (CAD) yet have impaired prognosis. We investigated whether routine assessment of coronary microvascular dysfunction (CMD) is feasible and predicts adverse outcome in women with angina and no obstructive CAD. Methods and results : After screening 7253, we included 1853 women with angina and no obstructive CAD on angiogram who were free of previous CAD, heart failure, or valvular heart disease in the prospective iPOWER (Improving Diagnosis and Treatment of Women with Angina Pectoris and Microvascular Disease) study. CMD was assessed by Doppler echocardiography in the left anterior descending artery as coronary flow velocity reserve (CFVR). Patients were followed for a composite outcome of cardiovascular death, myocardial infarction (MI), heart failure, stroke, and coronary revascularization. CFVR was obtained in 1681 patients (91%) and the median CFVR was 2.33 (quartiles 1–3: 2.00–2.74). During a median follow-up of 4.5 years, 96 events occurred. In univariate Cox regression, CFVR was associated with the composite outcome {hazard ratio (HR) 1.07 [95% confidence interval (CI) 1.03–1.11] per 0.1 unit decrease in CFVR; P  < 0.001}, primarily driven by an increased risk of MI and heart failure. Results remained significant in multivariate analysis [HR 1.05 (95% CI 1.01–1.09) per 0.1 unit decrease in CFVR; P  = 0.01]. In exploratory analyses, CFVR was also associated with the risk of repeated hospital admission for angina and all-cause mortality. Conclusion : Assessment of CFVR by echocardiography is feasible and predictive of adverse outcome in women with angina and no obstructive CAD. Results support a more aggressive preventive management of these patients and underline the need for trials targeting CMD. Graphical Abstract: